Answers

2014-04-09T07:28:56+05:30
Alpha & beta are the zeros of the polynomial and 
α+β=6 and αβ=4
therefore the required polynomial is x^2 - (α+β)x + αβ = 0
                                                 =x^2 - 6x + 4 = 0
x^2 - 6x + 4 = 0 is the required polynomial.
2 4 2
Comment has been deleted
Comment has been deleted
Comment has been deleted
Comment has been deleted
Comment has been deleted
2014-04-09T15:46:33+05:30
To get this quadratic equation in polynomial form , it can be written as 

α + β = 6  ,  α β = 4

x^2 - ( α + β) x + αβ = 0
 x^2 - 6 x  + 4 = 0


1 4 1